Performance of Eggshell Powder Addition to Clay Soil for Stabilization - Munirwan, Reza Pahlevi; Putra Jaya, Ramadhansyah; Munirwansyah, .; Ruslan, . (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
The behavior of clay soil often becomes problematic for the building above it. One problem is its shrinking and swelling behavior which is affected by its water content, which also frequently influences the soil bearing of capacity in holding the load of the building above it. The powder from eggshell which abbreviated as ESP is a food industry waste that is high calcium and not often used for reprocessing. This experiment purposes is to know the effect of adding ESP as a stabilizing material in clay. Soil sample for laboratory testing was carried out from Cot Bagie Village, Blang Bintang, Aceh Besar District, and Aceh Province. From AASHTO classification system, the soil sample is A-7-5 (21) and from USCS system, is organic clay with high plasticity (OH). The percentages of ESP added are 0%, 3%, 6% and 9% of the dry weight of the clay for experiment on laboratory. The Atterberg Limit parameters commonly incline with ESP addition. Based on the standard Proctor test, the original soil has an Optimum Moisture Content (OMC) of 19.8% and a maximum dry unit weight (γd max) of 1.367 gr/cm3 . Overall, adding ESP to the clay sample increases the mechanical properties of soil compared to the sample without ESP. Thus, the use of ESP for stabilization in this experiment can improve the bearing capacity, so that it is beneficial for construction in the field.